Bioactive Glass S53P4 Alternatives to Autolo-gous Bone Graft in the Management of Large Bone Defects in Children. - Mohd Anuar Ramdhan, Ibrahim; Faris Indra Prahasta, Didi Indra; Muhammad Lutfi, Abdul Rashid (The Brunei International Medical Journal (BIMJ), 2024)
Traumatic bone defects in children are rare, occurring immediately post-trauma or secondary to infected non-union. Autologous bone graft is considered the gold standard and is widely used during the second stage of one of the techniques known as the induced membrane technique. Bioactive glass S53P4 has been proven to share similarities with autografts, especially in the for-mation of new bone. Its ability to provide local control of infection through antibacterial properties sets it apart from other types of synthetic bone grafts. We utilized bioactive glass S53P4 granules alone in the second stage of the induced membrane technique in a child, resulting in a favorable outcome. The use of bioactive glass S53P4 granules proves practical in cases where a substantial amount of bone graft is needed to fill more significant bone defects, thereby avoiding donor site morbidity.